2023
DOI: 10.3390/ijms242015352
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Recent Advances in Nano-Based Ocular Drug Delivery

Li-Ching Liu,
Yi-Hao Chen,
Da-Wen Lu

Abstract: Ocular diseases profoundly impact patients’ vision and overall quality of life globally. However, effective ocular drug delivery presents formidable challenges within clinical pharmacology and biomaterial science, primarily due to the intricate anatomical and physiological barriers unique to the eye. In this comprehensive review, we aim to shed light on the anatomical and physiological features of the eye, emphasizing the natural barriers it presents to drug administration. Our goal is to provide a thorough ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 183 publications
0
6
0
Order By: Relevance
“…Eye drops are a common treatment for the Dry Eye, but their effectiveness is limited [ 15 , 219 ]. In the study of Xu et al, dexamethasone-loaded lacrimal plug was prepared by 3D printing technology, which was composed of polyethylene glycol diacrylate (PEGDA) and polyethylene glycol 400 (PEG 400), which realized the loading of different concentrations of drugs by creating a semi-interpenetrating network (semi-IPN) ( Fig.…”
Section: Application Of Photo-crosslink Hydrogels In Ophthalmologymentioning
confidence: 99%
“…Eye drops are a common treatment for the Dry Eye, but their effectiveness is limited [ 15 , 219 ]. In the study of Xu et al, dexamethasone-loaded lacrimal plug was prepared by 3D printing technology, which was composed of polyethylene glycol diacrylate (PEGDA) and polyethylene glycol 400 (PEG 400), which realized the loading of different concentrations of drugs by creating a semi-interpenetrating network (semi-IPN) ( Fig.…”
Section: Application Of Photo-crosslink Hydrogels In Ophthalmologymentioning
confidence: 99%
“…Consequently, frequent injections are necessary, introducing operational risks such as conjunctival edema and subconjunctival hemorrhage [ 34 ]. The remaining periocular application methods, including posterior juxta scleral, retrobulbar, peribulbar, and sub-tenon applications, are primarily employed for anesthesia during ocular surgery [ 35 ]. It is noteworthy, however, that periocular administration still struggles to deliver an adequate amount of drugs to the retina due to losses occurring in the periocular space, the BRB, and the choroidal circulation, among other factors [ 33 , 34 , 35 ].…”
Section: Ocular Drug Administration Routesmentioning
confidence: 99%
“…As a result, these systems enhance the bioavailability and efficacy of the drug [ 65 ]. Many nano-based DDSs with distinct and specific characteristics have been developed so far [ 66 ].…”
Section: Nano-based Drug Delivery Systems In Dry Eye Diseasementioning
confidence: 99%
“…Nanosuspension technology offers a secure and efficient method of delivering hydrophobic drugs to the ocular surface. However, like nanoemulsions, enhancing the physical stability of these nanocarriers is crucial for their practicality [ 66 , 78 ]. For instance, in the study conducted by Wu et al, the chitosan-modified mycophenolate mofetil nanosuspension showed decreased drug clearance compared to the non-chitosan-modified nanosuspensions [ 80 ].…”
Section: Nano-based Drug Delivery Systems In Dry Eye Diseasementioning
confidence: 99%